2007
DOI: 10.1021/jp0714973
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Aqueous Proline via Parallel Tempering Molecular Dynamics and Neutron Diffraction

Abstract: The structure of aqueous L-proline amino acid has been the subject of much debate centering on the validity of various proposed models, differing widely in the extent to which local and long-range correlations are present. Here, aqueous proline is investigated by atomistic, replica exchange molecular dynamics simulations, and the results are compared to neutron diffraction and small angle neutron scattering (SANS) data, which have been reported recently (McLain, S.; Soper, A.; Terry, A.; Watts, A. J. Phys. Che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 35 publications
4
29
0
Order By: Relevance
“…56,57 In contrast to these assumptions, our results indicate that protectants like TMAO preferentially accumulate around macromolecules which results in a preferential hydration of PNIPAM due to the strong kosmotropic and hygroscopic properties of TMAO. In fact, this mechanism, which was suggested for other co-solutes like cryoprotectants, 58,59 is in good agreement with the experimental results and allows us a qualitative explanation and interpretation of the DLS measurements. We also studied the influence of urea on PNIPAM by DLS experiments which additionally verifies our proposed mechanism due to the observed deviations from the results found for TMAO.…”
Section: Introductionsupporting
confidence: 85%
“…56,57 In contrast to these assumptions, our results indicate that protectants like TMAO preferentially accumulate around macromolecules which results in a preferential hydration of PNIPAM due to the strong kosmotropic and hygroscopic properties of TMAO. In fact, this mechanism, which was suggested for other co-solutes like cryoprotectants, 58,59 is in good agreement with the experimental results and allows us a qualitative explanation and interpretation of the DLS measurements. We also studied the influence of urea on PNIPAM by DLS experiments which additionally verifies our proposed mechanism due to the observed deviations from the results found for TMAO.…”
Section: Introductionsupporting
confidence: 85%
“…Both SANS and wideangle scattering studies were carried out on the same solutions and although the formation of larger transient clusters of proline [38,39] and glutamine [40] were observed during modelling of the wide angle scattering data and in MD simulations, no larger scale structures were found in the SANS data.…”
Section: Solution Self-assembly Of Larger Amphiphilesmentioning
confidence: 98%
“…9) the dipole moments of the two constituting Pro molecules should be practically anti-parallel. Based on results from various techniques Troitzsch et al 16,18,19 also found evidence for dimeric structures at high Pro concentrations, in particular at low temperature. However, they found no evidence for mesoscale aggregation postulated on the basis of spectroscopic and calorimetric data.…”
Section: View Article Onlinementioning
confidence: 96%
“…Despite considerable efforts during the last decade to understand Pro-water interactions only a few publications describe its hydration structure. 6,7,[15][16][17][18][19][20][21][22][23][24][25] Moreover, the available quantitative information is scattered considerably. For instance, hydration numbers range from 20, obtained in a MD simulation, 15 to 11-12 from statistical mechanics 23 to 8-9, obtained with neutron diffraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation